Jedidiah Morse and the Transformation of Print Culture in New England, 1784-1826. - JACKSON, LEON (Early American Literature, 1999)
Provides an essay that discusses the three cultures of printing manuscripts in New England from 1784 to 1826. Brief biography of Minister Jedidiah Morse in order to gain understanding of printing; Morse and the commercialization of religious controversy.